Effect of (2)H and (18)O water isotopes in kinesin-1 gliding assay - Maloney, Andy (PeerJ Inc., 2014)
We show for the first time the effects of heavy-hydrogen water ((2)H(2)O) and heavy-oxygen water (H(2)(18)O) on the gliding speed of microtubules on kinesin-1 coated surfaces. Increased fractions of isotopic waters used in the motility solution decreased the gliding speed of microtubules by a maximum of 21% for heavy-hydrogen and 5% for heavy-oxygen water. We also show that gliding microtubule speed returns to its original speed after being treated with heavy-hydrogen water. We discuss possible interpretations of these results and the importance for future studies of water effects on kinesin and microtubules. We also discuss the implication for using heavy waters in biomolecular devices incorporating molecular motors.